THE EFFECT OF THERMAL RESISTANCE OF CEILING LAYER ON THE PERFORMANCE OF AN AIR CONDITIONER AND ROOM TEMPERATURE DISTRIBUTION - Siang, Jeri Tangalajuk; Patabang, Daud (Jurnal Rekayasa Mesin, 2024)
The effectiveness of an air conditioner does not only depend on the design of the air-conditioner solely. Several factors affect the effectiveness of the cooling process of a room. One of the main factors in obtaining optimal results in the cooling process of a room is the rate of heat flow that enters a conditioned space. The amount of heat flow that enters a conditioned room affects the final temperature of the room. The ceiling is a part of the room that has a immense heat-flow rate. That is because the air temperature above the plafond is relatively high, and the thickness of the room plafond is relatively compact. It is necessary to analyze the room plafond material thermal resistance in increasing the heat absorbtion efficiency of household air conditioners. The thermal resistance of the material effect on the average room temperature, room temperature map, and the energy consumption is examined experimentally. The result shows that by occupying the plafond with a Styrofoam layer, the average room temperature decreases by 1.3⁰C, the air conditioner cooling capacity decreases by 0.402 kW, electric current decreases by 0.006 A compared to the existing room condition.